Blood Compatibility of PET Fabric Modified by Surface Grafting (Journal of Fiber Bioengineering and Informatics, 2018)
In order to improve the blood compatibility of Poly (Ethylene Terephthalate) (PET) fabric purposed foran artificial heart valve sewing ring, the grafting of Acrylic Acid (AA) and Polyethylene Glycol (PEG) onPET fabric by Ultraviolet (UV) irradiation has been studied. The influences of UV irradiation time, UVirradiation intensity and the concentration of acrylic acid have been investigated. The results revealedthat acrylic acid was successfully grafted onto the surface of PET fabric and the blood compatibilityof PET fabric was effectively improved. The blood compatibility tests suggested that UV irradiationmethod can effectively induce PEG onto the surface of AA modified PET to further prolong the ActivatedPartial Thromboplastin Time (APTT), Prothrombin Time (PT) and Thrombin Time (TT).
Keywords: Poly (Ethylene Terephthalate) Fabric; Acrylic Acid; UV; Grafting; Polyethylene Glycol